Development of hybrid model of coordinating decision-making formation for realization of manufacturing process at instrument-making enterprises - Собчак, Андрей Павлович; Шостак, Игорь Владимирович; Шабанова-Кушнаренко, Любовь Владимировна (Technology audit and production reserves, 2016)
This paper discusses the decision support system, as a concept, structure and features of the use of information technologies, decision-making methods and the possible use of a decision support system according to experience and application of the methodology of SME «KIATON». The aim of this research is forming a hybrid model of coordinating decision-making in the implementation of the production process at the instrument-making enterprises by providing a computer-aided algorithm of the hybrid agent. The method of formation of the coordinating decision-making formation was synthesized with the help of the extended model to reconcile the results of the decisions of local manufacturing subsystems that manufactures assembly units. Hybrid approach to the synthesis of model of coordinating decision-making formation for the rational organization of the production process of tools at the instrument-making enterprises is considered. This model makes it possible to identify and resolve conflicts that arise in the production process. It is shown that the hybrid model can be used as a part of the intellectual core of decision support systems in production management.